1997
DOI: 10.1007/bf02406154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humic acid on transport and transformation of mercury in soil-plant systems

Abstract: Abstract. The influence of humic acid (HA) on the transport and transformation of mercury (Hg) in soil was studied. No available Hg could be detected (<2.5 #g kg-t ) in alluvial soil when the content of HA-carbon (HA-C) was higher than 0.2 g kg-i although a large amount of Hg (8 Itg kg-i ) was applied to the soil. The available Hg decreased with the increase of HA in purple soil (r=0.735). There are significant correlations between HA concentration and organic Hg in the tested soils (1-=-0.974 for the purple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 9 publications
2
28
0
Order By: Relevance
“…This is why we used bulk density, penetration resistance, shear resistance and soil porosity for measuring soil compaction. In agreement with the results of previous studies (Wang et al 1997, Williamson & Neilsen 2000, Wallbrink et al 2002, Han et al 2009), our findings showed that the investigated physical parameters of soil were significantly affected mainly by the first vehicle passes (comparison between Time 1 and Time 2). Further machine passes slightly increased or did not affect soil physical parameters.…”
Section: Discussionsupporting
confidence: 93%
“…This is why we used bulk density, penetration resistance, shear resistance and soil porosity for measuring soil compaction. In agreement with the results of previous studies (Wang et al 1997, Williamson & Neilsen 2000, Wallbrink et al 2002, Han et al 2009), our findings showed that the investigated physical parameters of soil were significantly affected mainly by the first vehicle passes (comparison between Time 1 and Time 2). Further machine passes slightly increased or did not affect soil physical parameters.…”
Section: Discussionsupporting
confidence: 93%
“…Wang et al (1997) observed that the increase of humus in soils affects the decrease of Hg content in plants, which could indicate strong binding of this element by organic matter. Montgomery et al (2000), however, found relatively high concentration of mobile and available mercury forms in soils with comparatively high amount of organic matter.…”
Section: Mercury Bound To Organic Mattermentioning
confidence: 99%
“…High content of clay fraction and Fe o , which forms soil sorption complex, leads to binding of mercury by the solid phase of the soil (Boszke et al 2003;Dreher and Follmer 2004). This fact does not limit mercury bioavailability when soil shows low amount of organic matter (Biester et al 2002a;Wang et al 1997). The process of mercury binding by clay minerals has been observed in soils containing a minimum of 15 % of clay (Wang et al 1997).…”
Section: Content Of Bioavailable Mercurymentioning
confidence: 99%
See 2 more Smart Citations